2023
DOI: 10.1038/s41467-023-35921-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of CLIMP-63 S-acylation control ER morphology

Abstract: The complex architecture of the endoplasmic reticulum (ER) comprises distinct dynamic features, many at the nanoscale, that enable the coexistence of the nuclear envelope, regions of dense sheets and a branched tubular network that spans the cytoplasm. A key player in the formation of ER sheets is cytoskeleton-linking membrane protein 63 (CLIMP-63). The mechanisms by which CLIMP-63 coordinates ER structure remain elusive. Here, we address the impact of S-acylation, a reversible post-translational lipid modific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…While different FA chain lengths, from C14 to C22, may be transferred to the target [9,43], the most frequently transferred FA is palmitate (16-carbon acyl chain) [44]; hence, S-acylation is often referred to as S-palmitoylation. Each ZDHHC enzyme displays a specific localization pattern throughout the endomembrane system, between the endoplasmic reticulum (ER) (e.g., ZDHHC4/6/7/9), the Golgi (e.g., ZDHHC3/4/8/2/20), [22,26,29] and the endocytic system, including the plasma membrane, endosomes, and vesicular structures (e.g., ZDHHC2/5/20) [22,26,45]. For some ZDHHCs, the subcellular distribution can be controlled by defined cytosolic motifs [46,47] but may vary between cell types or species [23,48,49].…”
Section: Zdhhc Acyl Transferasesmentioning
confidence: 99%
See 2 more Smart Citations
“…While different FA chain lengths, from C14 to C22, may be transferred to the target [9,43], the most frequently transferred FA is palmitate (16-carbon acyl chain) [44]; hence, S-acylation is often referred to as S-palmitoylation. Each ZDHHC enzyme displays a specific localization pattern throughout the endomembrane system, between the endoplasmic reticulum (ER) (e.g., ZDHHC4/6/7/9), the Golgi (e.g., ZDHHC3/4/8/2/20), [22,26,29] and the endocytic system, including the plasma membrane, endosomes, and vesicular structures (e.g., ZDHHC2/5/20) [22,26,45]. For some ZDHHCs, the subcellular distribution can be controlled by defined cytosolic motifs [46,47] but may vary between cell types or species [23,48,49].…”
Section: Zdhhc Acyl Transferasesmentioning
confidence: 99%
“…Both IP3R and CLIMP-63 interact with mitochondrial porin voltagedependent anion-selective channels (VDACs) at MCSs and coordinate ER-mitochondrial calcium exchanges [101] in an S-acylation dependent manner [100,102]. Interestingly, calnexin, CLIMP-63, IP3R, and TMX4 are all modified by the same acyltransferase, namely ZDHHC6 [22,52,103,104], which could act as a master regulator of some ER-mitochondrial contacts.…”
Section: S-acylation As An Orchestrator Of Membrane-membrane Communic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Quite recently, Kimura et al [ 31 ] discovered that DKK-3, as well as the other DKKs, physically bind to CKAP4 (cytoskeleton-associated protein 4, also known as P63, CLIMP-63 or ERGIC-63). CKAP4 is a type II transmembrane protein that is primarily expressed in the endoplasmic reticulum (ER) and regulates its architecture [ 32 ]. Yet, a minor fraction of CKAP4 (less than 10% of the total) is transported to the plasma membrane of specific cell types, including pulmonary, vascular smooth muscle, and bladder epithelial cells [ 33 ].…”
Section: Ckap4 Is the Only Known Receptor For Dkk-3mentioning
confidence: 99%
“…The tree was constructed using the neighbor-joining method and was visualized using iTOL ( Letunic and Bork, 2011 ). ZDHHCs are color-coded based on their reported subcellular localization(s) ( Abrami et al, 2017 , 2021 ; Ernst et al, 2018 ; Sandoz et al, 2023 ), and examples of substrates for each enzyme are shown in black (for a complete list of reported S-acylated proteins visit https://www.swisspalm.org/ [ Blanc et al, 2015 ]).…”
Section: Introductionmentioning
confidence: 99%